You are on page 1of 5

Solutions for Math 311 Assignment #2

(1) Find the principal argument and exponential form of


i
(a) z = ;
1+i

(b) z = 3 + i;
(c) z = 2 − i.
Answer. √
(a) Arg(z) = π/4 and z = ( 2/2) exp(πi/4)
(b) Arg(z) = π/6 and z = 2 exp(πi/6)

(c) Arg(z) = − tan−1 (1/2) and z = 5 exp(− tan−1 (1/2)i)

(2) Find all the complex roots of the equations


(a) z 6 = −9;
(b) z 2 + 2z + (1 − i) = 0.
Solution.
(a) The roots are
√ √6

z = 6 −9 = 9eπi = 3eπi/6 e2mπi/6 (m = 0, 1, 2, 3, 4, 5)
3

√ √ √ √
35/6 3
3 √3 35/6 3
3 35/6 3
3 √
3 35/6 3
3
= + i, 3i, − + i, − − i, − 3i, − i.
2 2 2 2 2 2 2 2
(b) The roots are

p
−2 + 4 − 4(1 − i)
z= = −1 + i
√ 2
= −1 + eπi/2 = −1 + eπi/4 e2mπi/2 (m = 0, 1)
√ ! √ √ ! √
2 2 2 2
= −1 + + i, −1 − − i.
2 2 2 2

(3) Sketch the curves in the complex plane given by


(a) Im(z) = −1;
(b) |z − 1| = |z + i|;
(c) 2|z| = |z − 2|.
Solution. Let z = x + yi.
(a) {Im(z) = −1} = {y = −1} is the horizontal line passing
through the point −i.
1
2

(b) Since

|z − 1| = |z + i| ⇔ |(x − 1) + yi| = |x + (y + 1)i|


⇔ |(x − 1) + yi|2 = |x + (y + 1)i|2
⇔ (x − 1)2 + y 2 = x2 + (y + 1)2 ⇔ x + y = 0,

the curve is the line x + y = 0.


(c) Since

2|z| = |z − 2| ⇔ 2|x + yi| = |(x − 2) + yi|


⇔ 4|x + yi|2 = |(x − 2) + yi|2
⇔ 4(x2 + y 2 ) = (x − 2)2 + y 2 ⇔ 3x2 + 4x + 3y 2 = 4
 2
2 2 16 2 4
⇔ x+ +y = ⇔ z + =

3 9 3 3

the curve is the circle with center at −2/3 and radius 4/3.

(4) Do the following:


(a) Use exponential form to compute
√ 2011
(i) (1 + √3i) ;
(ii) (1 + 3i)−2011 .
(b) Prove that

1005  
X 2011
(−3)m = 22010
m=0
2m

and
1005  
X 2011
(−3)m = 22010 .
m=0
2m + 1

Solution. Since
√ !

 
1 3 πi
1+ 3i = 2 + i = 2 exp ,
2 2 3
3

we have
√ 2011
   
2011 2011πi 2011 2011πi
(1 + 3i) =2 exp =2 exp
3 3
 
πi
= 22011 exp 670πi +
3
  √ !
πi 1 3
= 22011 exp = 22011 + i
3 2 2

= 22010 (1 + 3i).
Similarly,
√ −2011 √
(1 + 3i) = 2−2013 (1 − 3i).
By HW 1 #6,
√ √
22010 (1 + 3i) = (1 + 3i)2011
1005  1005 

 
X 2011 m
X 2011
= (−3) + i (−3)m 3.
m=0
2m m=0
2m + 1
It follows that
1005   1005  
X 2011 m
X 2011
(−3) = (−3)m = 22010 .
m=0
2m m=0
2m + 1

(5) Show that


R4 − R
4 4
z + iz
≤ ≤ R +R
R2 + R + 1 z 2 + z + 1 (R − 1)2
for all z satisfying |z| = R > 1.

Proof. When |z| = R > 1,


|z 4 + iz| ≥ |z 4 | − |iz| = |z|4 − |i||z| = R4 − R
and
|z 2 + z + 1| ≤ |z 2 | + |z| + |1| = |z|2 + |z| + 1 = R2 + R + 1
by triangle inequality. Hence
4 4
≥ R −R .
z + iz

z 2 + z + 1 R2 + R + 1
On the other hand,
|z 4 + iz| ≤ |z 4 | + |iz| = |z|4 + |i||z| = R4 + R
4

and
√ ! √ !
−1 + 3i −1 − 3i
|z 2 + z + 1| = z − z−

2 2


√ √
−1 + 3i −1 − 3i
= z − z −

2 2


−1 + √3i −1 − √3i
! !
≥ |z| − |z| −

2 2


= (R − 1)(R − 1) = (R − 1)2
Therefore, 4 4

z + iz
≤ R +R .
z 2 + z + 1 (R − 1)2


(6) Use complex numbers to prove Law of Cosine: Let ∆ABC be


a triangle with |BC| = a, |CA| = b, |AB| = c and ∠BCA = θ.
Then
a2 + b2 − 2ab cos θ = c2 .
Hint: Place C at the origin, B at z1 and A at z2 . Prove that
z1 z 2 + z2 z 1 = 2|z1 z2 | cos θ.

Proof. Following the hint, we let C = 0, B = z1 and A = z2 .


Then a = |z1 |, b = |z2 | and c = |z2 − z1 |. So
a2 + b2 − c2 = |z1 |2 + |z2 |2 − |z2 − z1 |2
= (z1 z 1 + z2 z 2 ) − (z2 − z1 )(z2 − z1 )
= (z1 z 1 + z2 z 2 ) − (z2 − z1 )(z 2 − z 1 )
= (z1 z 1 + z2 z 2 ) − (z1 z 1 + z2 z 2 − z1 z 2 − z2 z 1 )
= z1 z 2 + z2 z 1 .
Let z1 = r1 eiθ1 and z2 = r2 eiθ2 . Then
z1 z 2 + z2 z 1 = r1 eiθ1 r2 eiθ2 + r2 eiθ2 r1 eiθ1
= (r1 eiθ1 )(r2 e−iθ2 ) + (r2 eiθ2 )(r1 e−iθ1 )
= r1 r2 ei(θ1 −θ2 ) + r1 r2 ei(θ2 −θ1 )
= 2r1 r2 cos(θ1 − θ2 ) = 2|z1 ||z2 | cos θ = 2ab cos θ.
5

Therefore, we have
a2 + b2 − c2 = z1 z 2 + z2 z 1 = 2ab cos θ
and hence
a2 + b2 − 2ab cos θ = c2 .